Patrones de diversidad alfa en tres fragmentos de bosques montanos en la región norte de los Andes, Colombia - López, Wilson; Duque, Álvaro (Revista de Biología Tropical, 2010)
Diversity studies in forests are useful for conservation management. We analyzed the patterns of alpha diversity in three protected forests along an altitudinal gradient in the Northern part of the Central Mountain Range, Colombia. The study was based on six permanent plots of 1ha (two per area). According to plant size, two main categories were used: canopy (diameter at breast height>10cm) and understory (1cm<diameter at breast height<10cm). Species-area curves showed differences in species richness by size category in all regions. instead, species-individual curves were independent of the size in Anorí and Angelópolis, but not in Belmira. Diversity patterns, as measured by Fisher’s alpha index, showed a strong tendency to reach a plateau for sample sizes larger than 1000 individuals. Neither species-area curves nor species-individual curves showed an asymptote; however, the species accumulation rate in Belmira was very low (0.05) when compared to Anorí and Angelópolis (0.25). Fisher’s alpha index is a very useful tool to understand the extent of relative differences in diversity among regions or forest types along altitudinal gradients, even when sample size is relatively small. Our results sup-port dispersal limitation as the main mechanism structuring species assemblages at very fine scales, and the monotonic increment of density-dependence processes determining the tree community structure at larger spatial scales. Likewise, we found that density-dependence tends to increase with altitude.